Style and Themes in The Snow Child by Eowyn Ivey - Hrdina, Josef (Univerzita Pardubice, 2025)
The bachelor's thesis examines the novel "The Snow Child" by Eowyn Ivey and its use of myth in modern literature. It focuses on the ways in which the author constructs an ambiguous narrative and portrays the process of coping with personal loss using mythology elements. This analysis contributes to the discussion on the enduring function of myth as a significant interpretative tool in literature.
Keywords: pohádky; magický realismus; mnohoznačnost; zármutek a uzdravení; folktales; magic realism; ambiguity; grief and healing